Pemodelan Decision Modeling on Clothing Model Selection of Female Students of UIN Bukittinggi - , Adryan; Hary Syahbana; M. Fahri Akbar; Marselino Syahputra; Liza Efriyanti (SMART : Jurnal Teknologi Informasi dan Komputer, 2023)
The selection of clothing styles is a complicated decision for individuals including female students at uin bukittinggi in making this kind of decision there are many factors to be considered such as the weather the event to be attended comfort and fit along with personal style in this experiment we bring the monte carlo simulation method to model and analyze the clothing model selection decision of female students of uin bukittinggi we identify various variables that influence the decision such as temperature We identify various variables affecting the decision such as temperature weather type of event and personal preferences We determine the range of values for each variable define the appropriate probability distribution and generate random data based on the probability distribution Next we evaluate the choice of clothing models based on the generated random data and analyze the results The results of this monte carlo simulation can provide important insights for uin bukittinggi female college students in choosing clothing models that match their conditions and personal preferences